DETEKSI CEPAT KUALITAS INTERNAL PRODUK PERTANIAN SECARA NON DESTRUKTIF DENGAN LOW COST NEAR INFRARED SPEKTROSCOPY (STATE OF THE ART) - yunisa tri suci (AgriHumanis: Journal of Agriculture and Human Resource Development Studies, 2023)
The quality of agricultural products is demanded to be more optimal in the midst of an increasingly competitive economic development where this is determined by the internal and external quality of these products. Several conventional methods for detecting internal and external qualities have their respective drawbacks. One of the methods to detect the internal and external quality of agricultural products is the near infrared spectroscopy method. With advances in technology such as MEMS-based nanoimprint lithography, compact and microcontrollers, 3d printing, and wireless technology, it is possible to realize portable detection systems. Along with the development of technology, electronic components have also experienced miniaturization, the size of the spectroscopic device has also become smaller. Development and sale of several handheld spectrometers, which include becoming smaller, lighter, and cheaper, such as the use of a single array detector for the development of low cost near infrared handhelds for various agricultural commodities